2007
DOI: 10.1113/jphysiol.2007.135871
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes associated cell stress and dysfunction: role of mitochondrial and non‐mitochondrial ROS production and activity

Abstract: It is now widely accepted, given the current weight of experimental evidence, that reactive oxygen species (ROS) contribute to cell and tissue dysfunction and damage caused by glucolipotoxicity in diabetes. The source of ROS in the insulin secreting pancreatic β-cells and in the cells which are targets for insulin action has been considered to be the mitochondrial electron transport chain. While this source is undoubtably important, we provide additional information and evidence for NADPH oxidase-dependent gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
437
0
20

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 591 publications
(463 citation statements)
references
References 163 publications
(175 reference statements)
6
437
0
20
Order By: Relevance
“…In patients with type 2 diabetes, there is, over time, a progressive loss of beta cells due to increased apoptosis [39][40][41][42]. This increase in cell death is thought to be a consequence, at least in part, of glucolipotoxicity and associated oxidative stress [20,21,43,44]. There is, nonetheless, much that remains unknown regarding the mechanisms of beta cell loss as diabetes progresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with type 2 diabetes, there is, over time, a progressive loss of beta cells due to increased apoptosis [39][40][41][42]. This increase in cell death is thought to be a consequence, at least in part, of glucolipotoxicity and associated oxidative stress [20,21,43,44]. There is, nonetheless, much that remains unknown regarding the mechanisms of beta cell loss as diabetes progresses.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with type 2 diabetes lose a significant portion of their beta cell mass over time [18,19], and this is believed to be at least in part a consequence of oxidative stress [20,21]. Various lines of indirect evidence suggest that pharmacological interventions that augment glucokinase activity may favour mechanisms that slow or prevent beta cell loss [22,23] or promote beta cell proliferation in vivo [3,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Certain studies have found increased lipid peroxides or ROS and oxidative stress (or both) in different animal models of diabetes (Anjaneyulu and Chopra 2004;Mehta et al 2006). However, the results in clinical practice are not unequivocal and the usefulness of antioxidant therapy in diabetic patients is not convincing (Newsholme et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the shunting of fatty acid towards esterification may provide a protective mechanism against the detrimental effects of lipid overload and elevated β-oxidation [29][30][31][32]. This may prevent the build-up of ROS or products of incomplete β-oxidation, such as specific acylcarnitine esters, which have been linked to insulin resistance [33,34]. A reduction in β-oxidation in association with improved insulin sensitivity has been described predominantly in muscle [31,34] and is in direct contrast to other findings indicating a positive role for β-oxidation [35][36][37].…”
Section: Discussionmentioning
confidence: 99%